2006
DOI: 10.1007/s10535-006-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water stress on photosystem 2 in two wheat cultivars

Abstract: The effects of osmotic dehydration on the photochemical activity, gene transcription, and protein content of photosystem 2 (PS 2) in leaves of two wheat (Triticum aestivum L.) cultivars Miannnong No. 4 and No. 5 were studied. Roots of both cultivars were submerged into polyethylene glycol (PEG) solutions with an osmotic potential of -0.5 MPa for 0, 24, 48, and 72 h. Relative water content (RWC) decreased markedly after 48 and 72 h. Simultaneously, marked increase in electrolyte leakage, decrease in contents of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 35 publications
5
43
0
1
Order By: Relevance
“…If a plant is exposed to drought stress for a short period, Photosystem (PS) II will generate adaptation mechanism for preventing photoinhibition which is reflected by chlorophyll synthesis alteration [27]. Prolonged dehydration inhibits protein de novo synthesis and decreases gene transcriptions (such as psbA) [28]. In our results, exogenous AOS could induce LEA1 expression at early period to protect wheat from damage caused by drought stress.…”
Section: Discussionmentioning
confidence: 55%
“…If a plant is exposed to drought stress for a short period, Photosystem (PS) II will generate adaptation mechanism for preventing photoinhibition which is reflected by chlorophyll synthesis alteration [27]. Prolonged dehydration inhibits protein de novo synthesis and decreases gene transcriptions (such as psbA) [28]. In our results, exogenous AOS could induce LEA1 expression at early period to protect wheat from damage caused by drought stress.…”
Section: Discussionmentioning
confidence: 55%
“…It is noteworthy that in case of interaction between the increased temperatures and the drought the structural organization and regular processes in the cells of plants were broken in more degree [3,4]. Simultaneously, in condition of the water loss of wheat leaves, the roots of which were submerged into polyethylene glycol solutions, an increase in electrolyte leakage, decrease in contents of chlorophylls a and b, major PSII proteins, including the D1 and D2 proteins in the PSII and the LHC2 and I, whole inhibition of PSII activity were obtained [5]. Northern hybridization showed that progressive water stress remarkably reduced contents of the chloroplast gene psbA and psbD and nuclear gene cab transcripts [5] and 62 genes differentially expressed under osmotic stress [6].…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, in condition of the water loss of wheat leaves, the roots of which were submerged into polyethylene glycol solutions, an increase in electrolyte leakage, decrease in contents of chlorophylls a and b, major PSII proteins, including the D1 and D2 proteins in the PSII and the LHC2 and I, whole inhibition of PSII activity were obtained [5]. Northern hybridization showed that progressive water stress remarkably reduced contents of the chloroplast gene psbA and psbD and nuclear gene cab transcripts [5] and 62 genes differentially expressed under osmotic stress [6]. On the other hand, it was assumed that water stress had no effects on the primary photochemistry of PSII, but modified the PSII photochemistry in the light-adapted leaves and such modifications may be a mechanism to down-regulate the photosynthetic electron transport to match a decreased CO 2 assimilation [7].…”
Section: Introductionmentioning
confidence: 99%
“…The gene expression pattern identified for this metabolism corroborates to physiological conditions and could be used as an indicative of drought sensitivity for this Brazilian sugarcane cultivar. In plants where the loss of water relative content was small, the photochemical activity was less affected by water stress, supporting the concept of plant productivity loss under drought conditions (Liu et al, 2006). On the other hand, in the tolerant sugarcane cultivar SP83-2847 the photosynthetic rate decreased under mild stress, but several genes related to photosynthesis were induced under this condition, probably because the stress was not strong enough to produce www.intechopen.com photoinhibition.…”
Section: Genetic Analysismentioning
confidence: 52%